Spontaneous Lumbar Hernia: A Case Report - Mundhir Said Mohamed; Ramadhani Omari Abdalla (The Annals of African Surgery, 2023)
Lumbar hernias are rare, and the diagnosis can be easily missed. Acquired lumbar hernias can occur spontaneously; however, they are increasingly being reported due to trauma or flank surgery. A good history and examination can aid in diagnosis with imaging confirming the condition. Hernia repair can be laparoscopic or through open surgical approaches. We report a case of primary spontaneous lumbar hernia which was managed by an open approach to close the defect with retromuscular mesh placement.